RELIABILITY AND MICROSTRUCTURE ANALYSIS STUDY OF MESH WIRE FOR UNDERGROUND MINING SUPPORT PRODUCED BY PRE-GALVANIZED WIRE - WELD AND WELDED WIRE - HOT DIP GALVANIZED - Junwono, Renardi
Underground mining system is located in almost every mining industy situated at almost evey part of the world, including Indonesia. Without proper safety system implementation, the occurrence of mining accident risk probability will be high. The types of support generally implemented in underground mining consists of rock bolts, weld mesh, wire mesh, shotcrete, steel set & concrete, and timber. Wire mesh is held to the rock structure tied by plate-installed bolt. The installation of wire mesh in underground mines function as the support structure for the shotcrete and act as ground support that widen the falling rocks containment area. The main purpose of this research is to compare the quality difference between two variant of mesh wire, hot dip + weld (pre-galvanized) and weld + hot dip (galvanized). References related to the research topic regarding mesh wire are collected and analyzed, starting from the production procces until the application of mesh wire in underground mining. The main focus on the production stage of mesh wire falls on the mesh wire itself, the hot dip galvanization process, and the resistance spot welding (RSW) process. Analysis of microstructure and heat effect during the welding stage of post production mesh wire product are also necessary. From the references and testing data that have been analysed, the results show that the hot dip glavanization process yields changes of microstructure where the increase of the pearlite phase is observed and the formation of acicular ferrite phase in fusion zone occurs. Testing of the mechanical strength by yield strength, ultimate tensile strength, and ultimate shear strength testing reveals the same value of yield strength between pre-galvanized mesh wire and galvanized mesh wire, but ultimate tensile strength and ultimate shear strength value shows a more superior mechanical strength of pre-galvanized mesh wire compared to galvanized mesh wire. Measurement of both mesh wire coating thickness variant shows an even and relatively thin layer of coating in pre-galvanized mesh wire compared to galvanized mesh wire. Hardness value from testing indicates a similar hardness profile in both mesh wire variants when observing parts of the welding area. Mesh wire observation using SEM and EDS mapping at the fusion zone doesn’t indicate any sign of intermetallic phase formation in both mesh wire variant.